2022
DOI: 10.1186/s13054-022-04256-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of different targeted temperatures on out-of-hospital cardiac arrest outcomes in patients receiving extracorporeal membrane oxygenation: a nationwide cohort study

Abstract: Background Targeted temperature management (TTM) is recommended in the management of out-of-hospital cardiac arrest (OHCA) when coma persists after the return of spontaneous circulation. In the setting of extracorporeal membrane oxygenation (ECMO) for OHCA patients, TTM is associated with good neurological outcomes and is recommended in the Extracorporeal Life Support Organization guidelines. However, the optimal targeted temperature for these patients has not yet been adequately investigated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
0
11
1
Order By: Relevance
“…Watanabe et al 69 recently analyzed a retrospective cohort of 890 OHCA patients undergoing ECPR between 2014 and 2019; 249 patients were treated with NT (35–36 °C) and 641 with IH (32–34 °C). Whether by using multivariable logistic regression or inverse probability weighting, 30-day survival with favorable neurological outcome (CPC 1–2) was similar between the two groups (16.5% in the NT group and 15.9% in the IH group).…”
Section: Induced Hypothermia In Patients Undergoing Ecprmentioning
confidence: 99%
“…Watanabe et al 69 recently analyzed a retrospective cohort of 890 OHCA patients undergoing ECPR between 2014 and 2019; 249 patients were treated with NT (35–36 °C) and 641 with IH (32–34 °C). Whether by using multivariable logistic regression or inverse probability weighting, 30-day survival with favorable neurological outcome (CPC 1–2) was similar between the two groups (16.5% in the NT group and 15.9% in the IH group).…”
Section: Induced Hypothermia In Patients Undergoing Ecprmentioning
confidence: 99%
“…We express our gratitude to Hifumi and their associates for their interest in our manuscript pertaining to the utilization of targeted temperature management (TTM) among patients treated with extracorporeal membrane oxygenation (ECMO) [ 1 ].…”
Section: Dear Editormentioning
confidence: 99%
“…The study contained two groups of patients: those receiving normothermic TTM (n-TTM) (35–36 °C) and those receiving hypothermic TTM (h-TTM) (32–34 °C). No differences in 30-day favorable neurological outcomes [OR (95% CI) 1.01 (0.67–1.54)] or survival [OR (95% CI) 1.05 (0.76–1.46)] were observed between the two groups [ 1 ].…”
mentioning
confidence: 99%
“…In Japan, two studies on the use of ECPR for OHCA have recently been reported. The first is a retrospective observational study ( N = 890, 2014–2019) that used the JAAM-OHCA registry and included all kinds of OHCA patients [ 1 ]. The second is a retrospective registry study ( N = 1644, 2013–2018) with the largest number of ECPR patients in the world; it is known as the Study of Advanced life support for Ventricular fibrillation with Extracorporeal circulation in Japan (SAVE-J II) [ 2 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation